Rapid and sensitive method for the determination of acetaldehyde in fuel ethanol by high-performance liquid chromatography with UV-Vis detection - Saczk, A. A.; Okumura, L. L.; de Oliveira, M. F.; Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Springer, 2005)
A high-performance liquid chromatography (HPLC) method for the determination of acetaldehyde in fuel ethanol was developed. Acetaldehyde was derivatized with 0.900 mL 2,4-dinitrophenylhydrazine (DNPHi) reagent and 50 mu L phosphoric acid 1 mol L-1 at a controlled room temperature of 15 degrees C for 20 min. The separation of acetaldehyde- DNPH (ADNPH) was carried out on a Shimadzu Shim-pack C-18 column, using methanol/LiCl(aq) 1.0 mM (80/20, v/v) as a mobile phase under isocratic elution and UV-Vis detection at 365 nm. The standard curve of ADNPH was linear in the range 3-300 amg L-1 per injection (20 mu L) and the limit of detection (LOD) for acetaldehyde was 2.03 mu g L-1, with a correlation coefficient greater than 0.999 and a precision (relative standard deviation, RSD) of 5.6% (n=5). Recovery studies were performed by fortifying fuel samples with acetaldehyde at various concentrations and the results were in the range 98.7-102%, with a coefficient of variation (CV) from 0.2% to 7.2%. Several fuel samples collected from various gas stations were analyzed and the method was successfully applied to the analysis of acetaldehyde in fuel ethanol samples.
Keywords: high-performance liquid chromatography; UV-Vis detection; isocratic elution; acetaldehyde; 2,4-dinitrophenylhydrazine; fuel ethanol